A Descriptive Study of School-Based Problem-Solving. (March 2019) - Todd, Anne W.; Algozzine, Bob; Horner, Robert H.; Preston, Angela I.; Cusumano, Dale; Algozzine, Kate
We report here the type of problems and solutions that 38 school teams reported during a randomized wait-list controlled trial of one problem-solving approach (Team Initiated Problem Solving [TIPS]). The experimental results from that analysis are reported elsewhere. The purpose of this article is to summarize companion descriptive data from this analysis and suggest implications for school personnel and education researchers. Data for this analysis come from direct observation of team meetings for 38 elementary school teams in Oregon and North Carolina as they each met on four different occasions over an 18-month period to manage the behavioral supports in their schools. Our focus was on the types of problems the teams identified, the precision with which problems were identified (what behavior, who, where, when, why), the features of solutions that were developed, the extent to which solutions were perceived as being implemented, and the extent to which solutions were perceived as resulting in improved student outcomes. The most common solutions focused on varying forms of changing organizational systems. Teams were not likely to measure if their solution had been implemented or was effective prior to receiving TIPS training.